APLIKASI SAINS DAN TEKNOLOGI DALAM TRANSAKSI MUAMALAH ISLAM: RUJUKAN KEPADA RUKUN–RUKUN AKAD MENGIKUT PERSPEKTIF UNDANG–UNDANG KONTRAK ISLAM (Sains Humanika, 2008)
This article will discuss the application of science and technology used in the Islamic transaction (muamalah) in the present time and how such applications comply with the syarak justification in the context of Islamic Law of Contract. For that purpose, reference will be made to the main elements (principles/arkan) in the formation of contract itself. This article begins with a brief description regarding the application of science and technology in Islamic transactions, after which the discussion will concentrate on the main elements of contracts according to Islamic law of contract and to what extent and in what ways the principles are applied in Muamalah transactions in today’s science and technology development.
Keywords: Science and technology; Islamic transaction; Islamic law of contract; elements of contracts; Islamic law